Burnup computations of online-refueling process for pebble-bed reactors using layer-mixed-shell fuel movement model. (May 2019) - Wu, Shin-Rong; Wu, Shang-Chien; Chao, Der-Sheng; Liang, Jenq-Horng
Abstract: This study aims to propose a model for dynamically simulating the online-refueling process in pebble-bed reactor (PBR) using MCNPX. PBR has a special feature of online-refueling which can greatly reduce the outage time and enable a higher burnup in spent fuel. However, this feature also results in the dynamical fuel movements which may significantly increase the difficulty and the computational time in computer simulation. Therefore, an appropriate model is necessary to be proposed to simulate the burnup characteristics of online-refueling and to reduce the computational time simultaneously. All the calculations in this study were performed using MCNPX 2.7.0 with the ENDF/B-VII continuous energy nuclear data library. The PBR model was built according to the core design of HTR-10 but adopted some reasonable assumptions. The refueling process was emulated by utilizing the fuel loading scenario of the once through then out (OTTO) in combination with the layer-mixed-shell fuel movement. Additionally, the layer-mixed-shell fuel movement considered the concept of fuel channels, where the fuel pebbles only move in the same fuel channel, such that the burnup characteristics of fuel pebbles in both radial and axial direction can be identified separately. The core was divided into 9 fuel zones with a fixed volume and 3 fuel channels with a variety of fuel zones. Furthermore, the number of fuel zones in each fuel channel was determined based on the relative residence time of fuel pebbles in the core. The results revealed that the core can achieve an equilibrium fuel cycle after refueling several times, and after that all the core characteristics can nearly maintain unchanged between different cycles. Although the refueling process was modeled based on the OTTO fuel loading scenario instead of the multi-pass one, the discharged burnup can still reach the target burnup of the spent fuel for HTR-10, i.e. 72 GWd/tHM. In addition, the average discharged burnup under the equilibrium fuel cycle is approximate to 80 GWd/tHM, which also coincides the design value of the spent fuel for HTR-10. Therefore, the layer-mixed-shell movement model can consider the fuel movements in either radial or axial directions simultaneously and enable a more accurate prediction to the real refueling process of HTR-10 than our previous studies. Highlights: A proposed model for the dynamical simulation of PBR. Both the axial and burnup characteristics were performed. The core can achieve an equilibrium fuel cycle. The average discharged burnup can reach the design value of HTR-10.